(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
Student organisations within schools play an important role in shaping the character and developing the leadership skills of students. This study aims to analyse the role of student organisations in developing leadership skills among students at SMK Negeri 4 OKU. This study uses a qualitative descriptive method with a field study approach. Data was collected through observation, in-depth interviews, and documentation involving the student council, students, organisation advisors, and school officials. Data analysis was conducted through data reduction, data presentation, and conclusion drawing stages. The results showed that student organisations, such as the student council and extracurricular activities, played an active role in training students’ responsibility, discipline, communication skills, cooperation, and decision-making. Organisational activities provide students with direct experience in leading, managing activities, and solving problems collaboratively. Factors supporting leadership development include support from the school and organisation advisors, while inhibiting factors include time constraints and low participation among some students. This study concludes that student organisations are an effective means of fostering and developing leadership skills among students at school.